The Form of Character Education in Learning Dance at Sanggar Dance Students of Banyumas District - Okto Wijayanti; Ana Andriani (Universitas Cokroaminoto Palopo, 2020)
The research aimed to describe the form of character education in dance learning for students of Banyumas district dance studio. This research uses a qualitative method. The data collection techniques used were the interview method, the observation method, and the documentation method. Data analysis in this research was carried out when data collection took place, and after completing data collection within a certain period. The data analysis used in the research was the Miles and Huberman model. The research location is in the Dharmo Yuwono dance studio, Banyumas Regency. The results of the study are as follows 1) The teacher or dance coach always provides an example or role model so that students are really ready to receive dance learning in a dance studio. Learning settings are made fun and enjoyable. The role of teachers in character education in learning dance in dance studios is to guide students before and after learning dance at school and pay attention to students' enthusiasm for learning. The dance learning model used is a complete learning model, where the teacher teaches movements per unit, so that each meeting the students memorize part of their movements until they memorize it, then the movement is added until one dance has been memorized and mastered by the students properly and correctly.